2021
DOI: 10.1101/2021.09.03.458871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cell atlas of the fly kidney

Abstract: Like humans, insects rely on precise regulation of their internal environments to survive. The insect renal system consists of Malpighian tubules and nephrocytes that share similarities to the mammalian kidney. Studies of the Drosophila Malpighian tubules and nephrocytes have provided many insights into our understanding of the excretion of waste products, stem cell regeneration, protein reabsorption, and as human kidney disease models. Here, we analyzed single-nucleus RNA sequencing (snRNA-seq) data sets to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…With the advent of single-cell transcriptomics, providing data on both whole organisms ( 13 ) and individual tissues ( 7 , 19 , 20 ), it is worth emphasising some of the reasons why tissue transcriptomic atlases continue to be useful. For example, it has been demonstrated that whole-organism transcriptomics can severely under-represent tissue-specific expression ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of single-cell transcriptomics, providing data on both whole organisms ( 13 ) and individual tissues ( 7 , 19 , 20 ), it is worth emphasising some of the reasons why tissue transcriptomic atlases continue to be useful. For example, it has been demonstrated that whole-organism transcriptomics can severely under-represent tissue-specific expression ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent studies cubilin and amnionless have been identified to be expressed in mammalian podocytes and to be important for nephrocyte diaphragm remodelling in nephrocytes ( Prabakaran et al, 2012 ; Gianesello et al, 2017 ; Atienza-Manuel et al, 2021 ). Moreover, according to single nucleus RNA-seq in adult fly kidneys, nephrocytes do not show an overlap with murine proximal tubular cells, but with podocytes and parietal epithelium ( Xu et al, 2021 Preprint ). The recent data and several studies using nephrocytes support the concept of nephrocytes as podocyte equivalent, but similarities to proximal tubular cells cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of transcriptional profiles of distinct cell types has resulted in the development of single cell atlases across tissues, conditions, developmental stages (e.g. Allen et al, 2020;Brunet Avalos et al, 2019;Chen et al, 2021;Corrales et al, 2022;Hu, Tattikota, et al, 2021;Karaiskos et al, 2017;Li et al, 2022;Najle et al, 2023;Papatheodorou et al, 2020;Suo et al, 2022;Xu et al, 2021) and even for entire organisms (Li et al, 2022). Such single cell atlases can directly be used to ask whether genes identified in bulk RNAseq approaches may be expressed in specific cell types.…”
Section: Deconvolution: Merg Ing T Wo Wo Rldsmentioning
confidence: 99%